Morphology of the larval stages of the spider crab Herbstia condyliata (Fabricius, 1787) (Brachyura: Majoidea: Pisidae) obtained in laboratory conditions - Guerao, Guillermo; Abelló, Pere; Hispano, Coral (Zootaxa, 2008)
The complete larval development of the majoid crab Herbstia condyliata (Fabricius, 1787) from the western Mediterranean was obtained from laboratory culture. All larval stages (two zoeal stages and the megalopa) are described and illustrated in detail for the first time. The morphology of the zoeae and megalopa is compared with the corresponding stages of other known species of the family Pisidae. The zoeal stages of H. condyliata present a pleon with unusual characters within the Pisidae such as the presence of dorsolateral processes in pleomere 3, two dorsal setae in pleomeres 2–4 (second zoea) and the very long posterolateral processes in pleomeres 3–4. The megalopa can be differentiated from other Pisidae species by the presence of a very developed cardiac tubercle on the carapace and the absence of plumose setae on the basal segment of the first maxilliped exopod.